Mortality in U.S. Physicians Likely to Perform Fluoroscopy-guided Interventional Procedures Compared with Psychiatrists, 1979 to 2008 - Linet, Martha S. (Radiology, 2017)
PURPOSE: To compare total and cause-specific mortality rates between physicians likely to have performed fluoroscopy-guided interventional (FGI) procedures (referred to as FGI MDs) and psychiatrists to determine if any differences are consistent with known radiation risks. MATERIALS AND METHODS: Mortality risks were compared in nationwide cohorts of 45 634 FGI MDs and 64 401 psychiatrists. Cause of death was ascertained from the National Death Index. Poisson regression was used to estimate relative risks (RRs) and 95% confidence intervals (CIs) for FGI MDs versus psychiatrists, with adjustment (via stratification) for year of birth and attained age. RESULTS: During follow-up (1979–2008), 3506 FGI MDs (86 women) and 7814 psychiatrists (507 women) died. Compared with psychiatrists, FGI MDs had lower total (men: RR, 0.80 [95% CI: 0.77, 0.83]; women: RR, 0.80 [95% CI: 0.63, 1.00]) and cancer (men: RR, 0.92 [95% CI: 0.85, 0.99]; women: RR, 0.83 [95% CI: 0.58, 1.18]) mortality. Mortality because of specific types of cancer, total and specific types of circulatory diseases, and other causes were not elevated in FGI MDs compared with psychiatrists. On the basis of small numbers, leukemia mortality was elevated among male FGI MDs who graduated from medical school before 1940 (RR, 3.86; 95% CI: 1.21, 12.3). CONCLUSION: Overall, total deaths and deaths from specific causes were not elevated in FGI MDs compared with psychiatrists. These findings require confirmation in large cohort studies with individual doses, detailed work histories, and extended follow-up of the subjects to substantially older median age at exit. (©) RSNA, 2017 Online supplemental material is available for this article.